Clinical characteristics of children and young people admitted to hospital with covid-19 in United Kingdom: prospective multicentre observational cohort study - Swann, OV; Holden, KA; Turtle, L; Pollock, L; Fairfield, CJ; Drake, TM; Seth, S; Egan, C; Hardwick, HE; Halpin, S; Girvan, M; Donohue, C; et al. (BMJ, 2020)
Objective: To characterise the clinical features of children and young people admitted to hospital with laboratory confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in the UK and explore factors associated with admission to critical care, mortality, and development of multisystem inflammatory syndrome in children and adolescents temporarily related to coronavirus disease 2019 (covid-19) (MIS-C).